The Effect of Carbon Emission on Company Performance with Financial Slack as a Moderation Variable in Mining and Energy Sector Companies in Indonesia (2021-2025) - Laili Faizatussalamah; Indah Fajarini Sri Wahyuningrum (International Journal of Science and Environment (IJSE), 2026)
This study examines the effect of Carbon Emission Scope 1 and Carbon Emission Scope 2 on company performance and investigates the moderating role of Financial Slack. This study employed a quantitative approach using secondary data from the annual reports and sustainability reports of mining and energy companies listed in Indonesia during the 2021–2025 period. The sample was selected using purposive sampling, resulting in 42 companies (210 firm-year observations). Panel data regression analysis was conducted using the Fixed Effect Model (FEM). The results indicate that Carbon Emission Scope 1 has a positive and significant effect on company performance, while Carbon Emission Scope 2 has a negative and significant effect. Furthermore, Financial Slack significantly moderates the relationship between carbon emissions and company performance by weakening the effect of Carbon Emission Scope 1 and strengthening the effect of Carbon Emission Scope 2. These findings suggest that the impact of carbon emissions on company performance varies according to the type of emissions and that financial flexibility plays an important role in supporting sustainable corporate performance.